Business Process Analysis and Fraud Risk Management Design: A Case Study of PT. Global Intan Teknindo - Adhitya Ferdian Adha Adhitya Ferdian Adha; Achmad Ghazali (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Small and medium business (SMEs) are vulnerable to fraud especially when they have informal processes, unrecorded operating processes, and poor internal controls. The paper will explore the business processes within PT Global Intan Teknido (GIT), a small distributor of industrial instruments, in an attempt to identify areas vulnerable to fraud and develop a suitable fraud prevention system. The qualitative exploratory case study took place through the use of in- depth interviews, first hand observation and analysis of documents of the owner, the sales and finance employees and the customers and the vendors. Business Process Mapping (BPM) was used to represent the As-Is workflow, Fraud Triangle Theory to help evaluate the behavioral drivers, benchmarking to compare practices with others of similar companies, and Fraud Risk Management (FRM) framework as the foundation of creating a Stop-Loss System. The results demonstrate the risk of fraud based on the undocumented requests to personal WhatsApp accounts, the lack of documentation regarding the communication with vendors, issuing quotations not related to the system, purchase orders made not in the system, the creation of the invoice by sales employees, and payment made by customers to personal bank accounts. Opportunity was the prevailing determinant as shown by Fraud Triangle analysis and reinforced by the sales pressure and rationalization pertaining to speed and customer demands. Benchmarking confirms that systemized documentation and systems of multi-level approval of documents will make the fraud exposure significantly less. This paper is informed by these points, hence the proposal of an FRM-based Stop-Loss System, which is comprised of preventive, detective, and corrective controls. The research increases the body of literature on SME fraud prevention through proving the possibility of combining business process analysis and FRM in developing an effective and resource-friendly control mechanism applied to small businesses.